2012
DOI: 10.3727/096368911x582769a
|View full text |Cite
|
Sign up to set email alerts
|

Local Transplantation of Granulocyte Colony-Stimulating Factor-Mobilized Human Peripheral Blood Mononuclear Cells for Unhealing Bone Fractures

Abstract: We previously reported the therapeutic potential of human peripheral blood (hPB) CD34 + cells for bone fracture healing via vasculogenesis/angiogenesis and osteogenesis. Transplantation of not only hPB CD34 + cells but also hPB total mononuclear cells (MNCs) has shown their therapeutic efficiency for enhancing ischemic neovascularization. Compared with transplantation of purified hPB CD34 + cells, transplantation of hPB MNCs is more attractive due to its simple method of cell isolation and inexpensive cost per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Therefore, a series of studies have explored the use of PB CD34+ cells or EPCs for bone fracture healing. 8386 Using a mouse bone fracture model, these studies first confirmed that fractures trigger EPC mobilization and incorporation into fracture sites. 83 The overlapping origin of endothelial and osteogenic markers was confirmed by Matsumoto et al 84 showing that about 20% of human peripheral blood CD34+ cells expressed the mRNA for OC.…”
Section: Circulating Calcifying Cd34+ Progenitor Cells and Epcsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, a series of studies have explored the use of PB CD34+ cells or EPCs for bone fracture healing. 8386 Using a mouse bone fracture model, these studies first confirmed that fractures trigger EPC mobilization and incorporation into fracture sites. 83 The overlapping origin of endothelial and osteogenic markers was confirmed by Matsumoto et al 84 showing that about 20% of human peripheral blood CD34+ cells expressed the mRNA for OC.…”
Section: Circulating Calcifying Cd34+ Progenitor Cells and Epcsmentioning
confidence: 83%
“…85 Importantly, CD34+ cells were more effective than mononuclear cells (MNCs) in inducing fracture healing, suggesting that stem/progenitor cell properties were involved. 86 Following these series of studies, researchers demonstrated fracture-induced mobilization of EPCs for bone healing in mice, rats, and humans. 8789 EPCs were also reported to contribute to bone healing in rat segmental bone defect model and critical-sized bone defects in sheep.…”
Section: Circulating Calcifying Cd34+ Progenitor Cells and Epcsmentioning
confidence: 99%
“…Infusion of the crude BM cells might cause similarly unfavorable events in the case of fracture. In addition, we reported the advantages of CD34 + cell transplantation over MNCs for fracture healing [21].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we attempted local transplantation of CD34 + cells with atelocollagen gel, a bioabsorbable scaffold, in the same animal model and demonstrated the similar effect at the lower dose compared with the systemic administration [20]. In addition, we reported the advantages of CD34 + cell transplantation over mononuclear cells (MNCs) for fracture healing [21].…”
Section: Introductionmentioning
confidence: 99%
“…In both of our previous studies focusing on the local transplantation of human GM-PB CD34 + cells and human GM-PB MNCs immediately after the fracture, immunohistochemistry and real-time RT-PCR for human-specific markers around the fracture sites indicated that one of the mechanisms underlying the angiogenic and osteogenic effects of these cells may be direct differentiation into endothelial and osteoblastic lineages. Furthermore, paracrine effects of the transplanted cells on resident cells were also proved by quantitative real-time RT-PCR for rat-specific primers for angiogenic and osteogenic growth factors or cytokines (14,48). Regarding the therapeutic potential of GM-PB MNCs and CD34 + cells for fracture healing, the union rate of fractures following human GM-PB MNC local transplantation in our previous study (33% at week 8) (14) was obviously lower compared with the union rate after human GM-PB CD34 + cell transplantation demonstrated in another study (100% at week 8) (48).…”
Section: Discussionmentioning
confidence: 99%